PENGARUH LITERASI DIGITAL TERHADAP KINERJA GURU SEKOLAH DASAR DENGAN WORK ENGAGEMENT SEBAGAI VARIABEL MEDIASI: Penelitian Kuantitatif - Nurhadi, Ahmad; Tito Parta Wibowo; Asep Agus Salim; Elim Halimah Sa’diyah; Noni Nurasiah; Rista Maifi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the effect of digital literacy on elementary school teachers’ performance with work engagement as a mediating variable. The study employed a quantitative approach using a survey design in Mandalawangi District, Pandeglang Regency. The sample consisted of 51 teachers from 7 elementary schools selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed through linear regression and mediation testing with IBM SPSS Statistics version 26. The findings indicate that digital literacy has a positive and significant effect on teacher performance (β = 0.853; p < 0.05). Digital literacy also has a significant effect on work engagement (β = 0.680; p < 0.05), and work engagement significantly affects teacher performance (β = 0.392; p < 0.05). The mediation analysis shows that work engagement partially mediates the relationship between digital literacy and teacher performance. These findings contribute to the development of a teacher performance improvement model that emphasizes both digital competence and work engagement in elementary education.